HTLV-1 associated T cell lymphoma in South East Asia: case report and family study. Issue 8 (August 1991) - Wang, T L; Liu, T C; Chan, L; Kueh, Y K; Wong, S Y
Abstract : Geographic clustering of human T cell lymphoma/leukaemia virus type 1 (HTLV-1) infection is well recognised, particularly in south western Japan, parts of West and Central Africa, the south eastern United States and the Caribbean islands. Sporadic cases have been reported in many other parts of the world. The first case of HTLV-1 associated leukaemia/lymphoma (ATLL) in South East Asia is reported. Contact tracing showed a high incidence of carriers among the relatives.